2016
DOI: 10.1177/0308575916669269
|View full text |Cite
|
Sign up to set email alerts
|

Maternal marital satisfaction during the first six months following international adoption

Abstract: International adoption can be a rewarding way for parents to build a family and many varied factors contribute to a positive adoption outcome. In particular, the period of adjustment just prior to and following an international adoption is a major transition for the adoptive family. Positive outcomes are related to both lower parental stress and higher marital satisfaction of the adoptive parents, and strong marital support is a protective factor ( Mainemer, Gilman and Ames, 1998 ). Examining the marital relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…While the present study’s results did not vary according to sociodemographic variables, findings indicated that older parents tend to report a lower parenting alliance. This result is consistent with previous work documenting that older age can be associated with lower parental well-being in mothers of an infant (e.g., Martin et al, 2016). Results also showed that fathers with more education and more children reported a lower parenting alliance.…”
Section: Discussionsupporting
confidence: 93%
“…While the present study’s results did not vary according to sociodemographic variables, findings indicated that older parents tend to report a lower parenting alliance. This result is consistent with previous work documenting that older age can be associated with lower parental well-being in mothers of an infant (e.g., Martin et al, 2016). Results also showed that fathers with more education and more children reported a lower parenting alliance.…”
Section: Discussionsupporting
confidence: 93%
“…Within the field of adoption, it seems somewhat surprising that the significance of the quality of the adoptive couple relationship has received so little explicit attention when compared to the extensive literature on adoptive parenting. Yet, in terms of positive outcomes for adoption, a supportive couple relationship that expresses their satisfaction with each other is key in helping couples manage the transition to adoptive parenthood and the challenges of raising an adopted child (Martin, Rosenhauer and Greco, 2016; Mooradian, et al., 2011). The aim of this study was, therefore, to evaluate the feasibility and preliminary evidence for effectiveness of the time-limited psychodynamic couple intervention for adoptive couples who were experiencing relationship distress.…”
Section: Discussionmentioning
confidence: 99%